Kesan Program Latihan Pembimbing Rakan Sebaya (PRS) Ke Atas Tahap Konsep Kendiri, Kemahiran Kaunseling Dan Orientasi Belajar Pelajar-pelajar - Othman Ab Rahman; Sapora Sipon; Roslee Ahmad (Global Academic Excellence, 2024)
This research was conducted to measure the effectiveness of Peer Counseling Training towards the subjects’ self-concept, counseling skill and study orientation. Ninety Form Four students from one of the boarding school was selected as the subject for this study. They have been divided randomly into three groups namely Group A, B and C. This experimental research commences with a pre-test given to the subjects using Tennessee Self-concept Scale:2, Counseling Skill Test and Study Orientation Scale. The Group A subject had the Type A treatment (Peer Counseling Training + Practical Session) whereas Group B subject only attended the Peer Counseling Training (Type B Treatment). Group C serve as the control group. At the end of the research the subject was given with a post-test using the same three instruments during the pre-test. The MANOVA analysis conducted on the pre-test score shows that there’s no significant difference between Group A, B and C’s self-concept, counseling skill and study orientation. However, the MANCOVA analysis conducted upon the post-test shows that there’s significant difference (p=0.000; p<0.05) between Group A, B and C’s self-concept, counseling skill and study orientation. The findings from this research also shows that there’s significant difference for subjects’ self-concept, counseling skill and study orientation between Group A and B even though their training difference is only by a practical session. The researcher finds that the existence of peer counseling group in educational institution will be able to improvise the level of counseling management. At the same time, it enhances the students’ leadership as they change to be an effective role model to their peer and thus leads to successful Muslim generation.